US Statement on Refugees: Press Release from US Delegation to the Twenty-Fourth Session of the UN Economic and Social Council in Geneva, Switzerland - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Neil Jacoby; United States. Mission to the United Nations Document enumerates aid provided by US to Hungarian refugees and stresses need to find permanent solutions to the crisis. Calls for the continuation of the mandate of the Office of the High Commissioner for Refugees and reappraisal of the UN Refugee Program.